2019
DOI: 10.1111/nph.15901
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropy in developmental regulation by flowering‐pathway genes: is it an evolutionary constraint?

Abstract: Summary Pleiotropy occurs when one gene influences more than one trait, contributing to genetic correlations among traits. Consequently, it is considered a constraint on the evolution of adaptive phenotypes because of potential antagonistic selection on correlated traits, or, alternatively, preservation of functional trait combinations. Such evolutionary constraints may be mitigated by the evolution of different functions of pleiotropic genes in their regulation of different traits. Arabidopsis thaliana flower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 180 publications
(190 reference statements)
1
54
0
Order By: Relevance
“…In this study, a number of genes were found whose expression was highly correlated with both seed traits, being putative candidate genes that could have a pleiotropic function governing both dormancy and longevity. In the ME2 module, the presence of genes controlling owering concurs with the concept of environmentally controlled pleiotropic role of owering in dormancy [76]. Also we found DORMANCY MAKER 1 (DRM1, Solyc03g006360.3.1), a auxin-regulated gene used as a marker of bud dormancy but not in Arabidopsis seed [77].…”
Section: Dormancy and Longevity Might Be Controlled By Pleiotropic Husupporting
confidence: 85%
“…In this study, a number of genes were found whose expression was highly correlated with both seed traits, being putative candidate genes that could have a pleiotropic function governing both dormancy and longevity. In the ME2 module, the presence of genes controlling owering concurs with the concept of environmentally controlled pleiotropic role of owering in dormancy [76]. Also we found DORMANCY MAKER 1 (DRM1, Solyc03g006360.3.1), a auxin-regulated gene used as a marker of bud dormancy but not in Arabidopsis seed [77].…”
Section: Dormancy and Longevity Might Be Controlled By Pleiotropic Husupporting
confidence: 85%
“…S11 and S12 and Tables S6 B and C). Pleiotropic effects of DOG1 on flowering and germination mediated by miR156 and miR172 may be a mechanism behind these trait correlations (60,76).…”
Section: Life-history Syndromes Resulted From Correlated Selection Onmentioning
confidence: 99%
“…FLC is a typical MADS-box gene that acts as a central repressor of floral transition in Arabidopsis [22]. In recent years, many of the components and environmental factors that influence the chromatin state of FLC, whether active or inactive, have been reported in model plants [18,19,31]. However, it is unknown which transcription factor drives the transcription of FLC.…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis, FLC is involved in the vernalization induction of flowering [17,18]. Without exposure to low temperature, FLC represses flowering by repressing flowering activators such as SOC1 and FT [18,19]. In perennial herbaceous plants, PERPETUAL FLOWERING1 (FLC homolog) is transiently repressed by low temperature to allow Arabis alpina to flower in the subsequent season, but then undergoes upregulation by warm temperature to limit flowering to only the spring season [20].…”
Section: Introductionmentioning
confidence: 99%